Indigenous language radio as a tool for improving functional and interactive health literacy at the community level - Onyenankeya, Kevin (Frontiers in Communication, 2026)
IntroductionIn South Africa, differences in education and the languages spoken constrain the improvement and promotion of health literacy. Therefore, health literacy initiatives face the arduous challenge of bridging the educational and language divide and providing equitable access to health information simultaneously. This article explored how indigenous language radio programming, such as Umhlobo Wenene’s (UWFM’s) Khanyisa Kukhanye Mhlobo show, could be leveraged to promote and improve functional and interactive among rural communities.MethodA qualitative methodology, grounded in the theory of self-efficacy was employed, and data were collected through a combination of in-depth interviews and audio content analysis.ResultsThe results suggest that Khanyisa Kukhanye Mhlobo can serve as a valuable media outlet for disseminating accurate and reliable health-related information to the public, particularly to marginalized communities. Using the first language or mother tongue and combining socially relevant health messages and stories that resonate with the listeners’ way of life and experiences makes the Show relatable and inspires trust, making the information more effective and actionable.DiscussionConsistent with previous findings, the study suggests that when health literacy is offered in a participatory manner and language spoken by the audience, it can increase the uptake of health information, modify behavior and empower individuals to participate actively in community health initiatives. The findings underscore the importance of public health agencies and NGOs utilizing indigenous language media platforms to deliver health literacy interventions. The results of this study provide insight into health literacy and behavior change among a specific African population and indigenous language radio, a medium rarely explored in mainstream academic endeavours.